Haemodynamic-energetic mechanism of sudden cardiac death in severe aortic stenosis: A modelling study - Dvoulety, Martin; Sitina, Michal (The Journal of physiology, 2025)
Severe aortic stenosis (AS) is a recognized risk factor for sudden cardiac death (SCD). Although ventricular tachyarrhythmias are the most common immediate cause of SCD, the majority of cases of SCD in patients with severe AS exhibited bradyarrhythmia as the primary rhythm. Enhanced activation of left ventricular baroreceptors (Bezold-Jarisch reflex) has been implicated in the pathogenesis of syncope in patients with AS. However, the precise mechanism by which an otherwise benign circulatory syncope can progress to cardiac arrest in severe AS remains unclear. This study proposes a haemodynamic-energetic mechanism to explain this progression, and demonstrates its plausibility using a mathematical model of cardiac haemodynamics and energetics. The model identifies states of cardiac energy imbalance, in which the energy expenditure of the heart exceeds the energy delivered to it. In individuals with a normal aortic valve, compensatory mechanisms can restore energy balance following syncope. By contrast, in severe AS, all conditions involving low peripheral vascular resistance are energetically unstable, regardless of compensatory response. Because energy imbalance is incompatible with sustained cardiac function, such states inevitably result in cardiac arrest. Importantly, the proposed mechanism does not require an exaggerated Bezold-Jarisch reflex, although the reflex probably acts as a trigger of syncope by initiating peripheral vasodilatation. Additionally, the limited coronary vasodilatory reserve commonly observed in severe AS significantly contributes to the development of myocardial energy imbalance. KEY POINTS: The precise mechanism of sudden cardiac death in patients with severe aortic stenosis remains uncertain. In the present study, we propose a novel haemodynamic-energetic mechanism of sudden cardiac death explaining how otherwise benign circulatory syncope can progress to cardiac arrest in patients with severe aortic stenosis. The plausibility of the mechanism is verified using a mathematical model. The model identifies states of cardiac energy imbalance in patients with severe aortic stenosis, where the energy expenditure of the heart exceeds the energy delivered to it, which inevitably leads to cardiac arrest. Mathematical simulation of a circulatory syncope reveals significant differences in the effects of compensatory response in patients with and without severe aortic stenosis. The results provide a comprehensive understanding of the mechanism of sudden cardiac death in patients with severe aortic stenosis.
Keywords: Bezold–Jarisch reflex; sudden death; aortic stenosis; cardiac energetics; mathematical model